KEMANFAATAN HUKUM DALAM PERIZINAN BERUSAHA BERBASIS RISIKO BAGI PELAKU USAHA - Francois Geny Ritonga; Mawar Sitohang (Honeste Vivere, 2026)
The administration of risk-based licensing—particularly following the implementation of the risk-based business licensing system as part of the enactment of Law No. 6 of 2023 on the Enactment of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation into Law (“Law 6/2023”) and Government Regulation No. 28 of 2025 on Risk-Based Business Licensing (“GR 28/2025”), provides legal benefits for business actors to drive the national economy and is a crucial aspect in creating a conducive investment climate for business actors. However, its implementation has faced obstacles that have impacted business licensing. This study is a normative legal study, and the research method used is a literature review examining relevant literature and legislation. The results of the study indicate that the enactment of GR 28/2025 provides legal benefits in risk-based business licensing for business operators.